2021
DOI: 10.1007/s13318-021-00738-5
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gegenqinlian Decoction on Pharmacokinetics and Pharmacodynamics of Atorvastatin Calcium in Hyperlipidemic Rats

Abstract: Background and Objectives Gegenqinlian decoction (GQD), a classic traditional Chinese medicine (TCM), was described in Shanghan Lun. GQD is often combined with antihyperlipidemic drugs (mainly atrovastatin calcium) in TCM clinics. However, the herb-drug interaction between GQD and atrovastatin calcium (AC) is still unknown. To determine whether the combination is safe, we evaluated the effects of GQD on the activities of cytochrome P450 (CYP) 3A2 enzyme and investigated the impact of GQD on the pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…( Chaudhary and Dion, 2013 ). On the other hand, PD analysis analyzes the drug effect and the mechanism of action of a new drug ( Cui et al, 2022 ). In order to understand the connection of particular components in a complex preparation with efficacy or toxicity, the precise study of the PK-PD relationship is valuable, Flavonoids have been proven to exert the protective effects, including antioxidant and anti-inflammatory effects, by eliminating the free radicals ( Rajendran et al, 2004 ; Nauser and Gebicki, 2019 ; Kejík et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Chaudhary and Dion, 2013 ). On the other hand, PD analysis analyzes the drug effect and the mechanism of action of a new drug ( Cui et al, 2022 ). In order to understand the connection of particular components in a complex preparation with efficacy or toxicity, the precise study of the PK-PD relationship is valuable, Flavonoids have been proven to exert the protective effects, including antioxidant and anti-inflammatory effects, by eliminating the free radicals ( Rajendran et al, 2004 ; Nauser and Gebicki, 2019 ; Kejík et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The filtrate was lyophilized further. The freeze‐dried powder of GQD was dissolved with 0.5% CMC‐Na before administration (1.35 g/kg of freeze‐dried powder equivalent to 3.5 g/kg of crude drugs) (Cui et al., 2022).…”
Section: Methodsmentioning
confidence: 99%
“…could affect the activity of CYP450 and transporter, which might cause HDIs (Kong et al., 2018; Liu et al., 2021; Wang et al., 2016). In our previous study, it was found that GQD could inhibit the activity of CPY3A2 in rats, increase the plasma exposure of atorvastatin when coadministrated in hyperlipidemic rats (Cui et al., 2022).…”
Section: Introductionmentioning
confidence: 99%